PENGARUH MODEL PEMBELAJARAN LOGAN AVENUE PROBLEM SOLVING (LAPS)-HEURISTIK TERHADAP KEMAMPUAN KOGNITIF DAN SOFT SKILL - Bichar Aritonang; Adi Sutopo (Universitas Negeri Medan, 2022)
Abstract This study aims to determine the differences in student learning outcomes of class XI TITL on the subject of Electrical Motor Installation by using the Logan Avenue Problem Solving (Laps)-Heuristic and Expository learning model. This research belongs to the type of quasi-experimental research. The population in this study were all students of class XI TITL SMK Negeri 1 Percut Sei Tuan, totaling 60 students. Sampling used a random sampling technique, with class XI TITL 1 as a group of 30 students in the Logan Avenue Problem Solving (Laps)-Heuristic learning model and class XI TITL 2 as a group of 30 students in the Expository learning method. The results showed that: there was a significant difference in the Logan Avenue Problem Solving (Laps)-Heuristic and Expository learning model on student learning outcomes with the subject of electric motor installation at SMK Negeri 1 Percut Sei Tuan. This is evidenced by the average cognitive learning outcomes of Logan Avenue Problem Solving (Laps)-Heuristics class students of 86.15 and an average soft skill of 85.7 while in the Expository class the cognitive learning outcomes are 78.65 and the average score is 78.65. soft skills of 80.9. The results of the statistical t-test with a significant level (α) = 0.05 obtained t-count learning outcomes of 4.071 and t-table = 2.002 so that tcount > ttable. The statistical results of the soft skills t-test with a significant level (α) = 0.05 obtained tcount 2,683 and ttable 2,002 so that tcount > ttable. The Logan Avenue Problem Solving (Laps)-Heuristic learning model is higher when taught than the Expository learning method on cognitive abilities and soft skills with electric motor installation subjects. Keywords: Cognitive Ability, Soft Skill Ability, Logan Avenue Problem Solving (Laps)-Heuristic, ExpositoryAbstrakPenelitian ini bertujuan untuk mengetahui perbedaan hasil belajar siswa kelas XI TITL pada mata pelajaran Instalasi Motor Listrik dengan menggunakan model pembelajaran Logan Avenue Problem Solving (Laps)-Heuristik dan Ekspositori. Penelitian ini termasuk jenis penelitian quasi experiment. Populasi dalam penelitian ini adalah seluruh siswa kelas XI TITL SMK Negeri 1 Percut Sei Tuan yang berjumlah 60 siswa. Pengambilan sampel digunakan teknik sampel random sampling, dengan kelas XI TITL 1 sebagai kelompok model pembelajaran Logan Avenue Problem Solving (Laps)-Heuristik yang berjumlah 30 orang siswa dan kelas XI TITL 2 sebagai kelompok metode pembelajaran Ekspositori yang berjumlah 30 orang siswa. Hasil penelitian menunjukkan bahwa: ada perbedaan yang signifikan model pembelajaran Logan Avenue Problem Solving (Laps)-Heuristik dan Ekspositori terhadap hasil belajar siswa dengan mata pelajaran instalasi motor listrik SMK Negeri 1 Percut Sei Tuan. Hal ini dibuktikan dangan rata-rata hasil belajar kognitif siswa kelas Logan Avenue Problem Solving (Laps)-Heuristik sebesar 86,15 dan rata-rata soft skill 85,7 sedangkan pada kelas Ekspositori hasil belajar kognitif sebesar 78,65 dan rata-rata nilai soft skill sebesar 80,9. Hasil statistik uji-t hitung dengan taraf signifikan (α) = 0,05 diperoleh thitung hasil belajar sebesar 4,071 dan ttabel = 2,002 sehingga thitung > ttabel. Hasil statistik uji-t soft skill dengan taraf signifikan (α) = 0,05 diperoleh thitung 2,683 dan ttabel 2,002 sehingga thitung > ttabel. Model pembelajaran Logan Avenue Problem Solving (Laps)-Heuristik lebih tinggi bila diajarkan dibanding dengan metode pembelajaran Ekspositori terhadap kemampuan kognitif dan soft skill dengan mata pelajaran instalasi motor listrik. Kata Kunci : Kemampuan Kognitif, Kemampuan Soft Skill, Logan Avenue Problem Solving (Laps)-Heuristik, Ekspositori